What Drives Innovation Activities in German SMEs in the Service and Production Sector? An Integration of Theoretical and Empirical Findings - Triller, Marcus; Vogel, Dennis; Fellmann, Michael (Complex Systems Informatics and Modeling Quarterly, 2023)
Innovation management is an essential prerequisite for the effective and efficient generation, planning, and implementation of ideas and thus for the further development of companies in a dynamic market and competitive environment. In order to investigate the internal innovation potential of production and service companies, this article examines basic success factors and challenges of innovation management in German small and medium-sized enterprises (SMEs) with a view to the sector to which they belong. On the basis of a questionnaire and interviews with experts, companies were considered with regard to their assessment of their innovative capacity. Based on an analysis of data from 30 participants, we show that the innovation capacity of SMEs with regard to success factors and challenges in production companies differs significantly from that of service companies. We also find that there is a discrepancy in the assessment of the potential for improvement of success factors and challenges. Our study shows that in the field of German SMEs, there is no “best way” to increase innovative capacity, but it depends on a combination of different factors.